은연어의 해수 순치에 따른 스트레스 반응의 변화 - 홍경표; 김병기; 전중균; 김유희; 박용주; 명정구; 김종만; Hong, Kyung-Pyo; Kim, Pyong-Kih; Jeon, Joong-Kyun; Kim, You-Hee; Park, Yong-Ju; et al. (Ocean and polar research, 2004)
Stress response to the seawater acclimation in coho salmon (Oncorhynchus kisutch) smolt was investigated. Salt concentration of rearing water was gradually increased for 3 days from freshwater to seawater (30 ppt salt level). The changes of serum concentrations of cortisol as a primary stress indicator, and as secondary indicators, glucose (GLC), lactate (LAC), triglyce.ide (TG), cholesterol (CHOL), sodium ion $(Na^+)$, chloride ion $(Cl^-)$ and enzyme activities (alanine aminotransferase, ALT: aspartate aminotrasferase, AST; lactate dehydrogenase, LDH) were quantified during the acclimation experiment. Among them, cortisol, LAC, TG, CHOL, ALT, AST concentrations showed rapid increase at the first exposure to the 10ppt salt level (day 1), and began to decrease to the constant values after day 2 of adaptation at 20ppt salt level. However, LDH concentration tended to decrease during the whole experimental period. $Na^+\;and\;Cl^-$ showed slight decrease at day 1, and increased to a little bit higher values after day 2 rather than those in freshwater. All the fishes started on taking a food after day 4 of seawater adaptation. From these results, to reduce osmotic shock inducible stress to fish in seawater acclimation, gradual increase of salt levels is recommended.